# Calculus

Find the anti-derivative of the integral
[3sqrt(x)(2x^2-4)]dx

1. 👍 0
2. 👎 0
3. 👁 75
1. ∫3√x (2x^2-4) dx
If we let
u = √x
du = 1/2√x dx
x = u^2

and we have
∫3√x (2x^2-4) dx
∫6x (2x^2-4) dx/2√x
∫6u^2(2u^4-4) du
and that's just power stuff.

1. 👍 0
2. 👎 0
posted by Steve

## Similar Questions

1. ### calc

find the area between the x-axis and the graph of the given function over the given interval: y = sqrt(9-x^2) over [-3,3] you need to do integration from -3 to 3. First you find the anti-derivative when you find the

asked by mikayla on April 18, 2007
2. ### Calculus

Find the anti-derivative of the integral [(7t^2+6t-15)/t^4]dt

asked by Anonymous on February 5, 2015
3. ### Calculus

Find the anti-derivative of the integral (7tan^2x+12)dx

asked by Anonymous on February 5, 2015
4. ### calculus

What is the definite integral from 0 to x of 1/(4 + t + 3t^2) dt? For starters, what is the anti-derivative and how did you find it? I think I could take it from there.

asked by Gabe on April 14, 2010
5. ### Sums-Calc

find the upper and lower bounds for definite integral sign, a=1, b=6, sqrt(x) dx. partitions are as follow: x0=1, x1= 3, x2=6 of the interval [1,6] upper sum: 3sqrt(3) + 3sqrt(6) lower sum: 3sqrt(3) + 3 but this is incorrect. can

asked by Eric on May 15, 2013
6. ### Upper-lower bounds-solved

find the upper and lower bounds for definite integral sign, a=1, b=6, sqrt(x) dx. partitions are as follow: x0=1, x1= 3, x2=6 of the interval [1,6] upper sum: 3sqrt(3) + 3sqrt(6) lower sum: 3sqrt(3) + 3 but this is incorrect. can

asked by Eric on May 15, 2013
7. ### Calculus

Find the anti derivative of the following: 1. u^-2(1-u^2+u^4)du 2. (sqrt(x)+ 3/x - 2e^(x))dx The anti derivative symbol is in front of the equations. Also need help on find f(x) so that it satisfies f'(x) = 1+e^x+1/x and f(1) =

asked by Rene on April 16, 2013
8. ### Pre-Cal

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 29, 2010
9. ### Pre-Cal(Urgent)

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 29, 2010
10. ### Pre-Cal

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 29, 2010

More Similar Questions